Informe final actividades del wp1 en guatemala en el marco de la iniciativa LCSR - Mena Urbina, Martin A.; Hernandez Quevedo, Monica; Van Der Hoek, Rein (2024)
This activity, part of the CGIAR Livestock and Climate initiative, aimed at evaluating the agronomic performance and nutritional quality of commercial grass cultivars in Puerto Barrios, Izabal, Guatemala.